2003
DOI: 10.3354/ame032165
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of free-living and attached bacteria in sediments colonized by Hediste diversicolor

Abstract: The dynamics of free-living and attached bacteria populations were studied in salt marsh sediments that were extensively colonized by the polychaete Hediste (Nereis) diversicolor (O. F. Müller). Bioturbation by H. diversicolor affected the density and community structure of free-living (FLB) and attached (AB) bacteria assemblages. Passage through the polychaete gut resulted in an 81 to 88% decrease of both bacterial groups and shift in favor of FLB in the hindgut (HG). In surficial sediments outside and inside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 45 publications
1
23
1
Order By: Relevance
“…Although it has been known that burrowing organisms affect sediment biogeochemistry, the interactions are often complex and detailed investigations on the effect of geochemical microzonations on microbial diversity are scarce (Kostka et al, 2002;Lucas et al, 2003;Matsui et al, 2004;Papaspyrou et al, 2006). This is not surprising because studies on microbial diversity in marine sediments have also only just begun (Mu mann et al, 2005;Wilms et al, 2006;Wu et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Although it has been known that burrowing organisms affect sediment biogeochemistry, the interactions are often complex and detailed investigations on the effect of geochemical microzonations on microbial diversity are scarce (Kostka et al, 2002;Lucas et al, 2003;Matsui et al, 2004;Papaspyrou et al, 2006). This is not surprising because studies on microbial diversity in marine sediments have also only just begun (Mu mann et al, 2005;Wilms et al, 2006;Wu et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Bacterial communities from the burrows of single species of nereidid worm, thalassinidean shrimp and fiddler crab (Lucas et al, 2003;Papaspyrou et al, 2005;Bertics and Ziebis, 2009, respectively) were found to be more similar to those in the surrounding subsurface sediment than to surface communities. In contrast, in this study the bacterial communities inhabiting the burrow wall more closely resembled those in surface rather than subsurface sediment.…”
Section: Figurementioning
confidence: 96%
“…data). Similarly, Lucas et al (2003) reported that the bacterial composition along the burrow walls of Nereis diversicolor is stable over time and markedly different from the community at the sediment surface. Even though microorganisms along burrow walls have to adapt to the rapidly oscillating redox environment due to the usually intermittent burrow ventilation (Kristensen 1988, Ziebis et al 1996, Furukawa 2001, our results confirm the idea that infaunal burrows, and ambient sediment, are stable environments over longterm periods compared to surface sediment, which is 188 Papaspyrou et al: Properties of Pestarella tyrrhena burrows continually disturbed by macrofaunal feeding, and current or wave mediated action (Kristensen 1988).…”
Section: Bacterial Abundance and Community Characteristicsmentioning
confidence: 99%